Classic Polemical Between the novel of Tenggelamnya Kapal Van Der Wijck and Magdalena - Fauzi Rahman (Universitas Indraprasta PGRI, 2017)
This study aims to determine the comparison between the novel Tenggelamnya Kapal van Der Wijck (TKVDW) by Hamka with Magdalena by Al-Manfaluthi. There was a calm question of Hamka's novel which was the result of a copy of the Magdalena. By the method of literary comparison, the results obtained are that indeed in both novels, there are similarities starting from the plot, the detail of the story, and the function of character. However, each story with a different social background ultimately shows its own story, ideas, and social details. Furthermore, regarding the similarity of the story and the rumors of plagiarism by Buya Hamka, there is indeed a plot resemblance, there are thoughts and ideas that remind Magdalena. But the reader must be intelligent and admit that in his narrative in the novel TKVDW, there is a culture of his own, his own experience, as well as his own problems.